Effects of the anchor bolts and soil flexibility on the seismic response of cylindrical steel liquid storage tanks. (15th July 2022) - Jaramillo, F.; Almazán, J.L.; Colombo, J.I.
Abstract: When cylindrical tanks are subjected to strong seismic excitations, the main characteristic that they present is the partial uplifting of the base plate due to the hydrodynamic pressure on the tank walls. This partial base uplifting occurs in both unanchored and anchored tanks, and can provoke several types of failure. A comprehensive analysis of the tank base uplifting implies considering different non-linearity mechanisms. This paper presents a simple and efficient model that takes into consideration the effects produced at the tank base (i.e., uplifting and rocking), as well as, the soil flexibility and the nonlinear effects at anchor system. A comprehensive analysis of the soil–foundation–structure interaction effects, in conjunction with the influence of the convective part of the fluid, was carried out for three anchored cylindrical steel tanks subjected to lateral seismic loads. First, a sinusoidal ground motion was applied to the tanks and the response was discussed for a better understanding of the model capabilities and the soil–foundation–structure interaction. Later, a 3D dynamic analysis was carried out and the effect of considering or not considering the convective component was evaluated. Three seismic ground motion and four different soil flexibilities were considered. Finally, a sensitivity analysis considering different number of anchor bolts in addition to the soil–foundation–structure interaction was performed for the slender tank. The non-linear simplified model proposed in this study was able to obtain a good estimate for the rocking resistance, the anchor bolt effects (considering post-yielding and gap opening/closing at the tank–foundation interface), soil flexibility and the stress distribution on the tank walls. The obtained results allow a better understanding of the seismic response of anchored tanks and shows that the soil–foundation–structure interaction reduces critical response parameters. However, the energy dissipation caused by the anchoring system is low, therefore, response modified factor is not expected in thin walled cylindrical liquid storage tanks. Finally, a certain minimum number of anchors is required to avoid failure due to buckling or excessive uplift. These results can motivates possible modifications in current seismic design codes, where energy dissipation technologies could be considered explicitly as a very promising alternative. Highlights: The influence of anchor bolts and soil type is evaluated in storage tanks. A simplified dynamic model for soil–foundation–tank interaction is proposed. Three different tank geometries placed on four different soil type were analyzed.